Why don't we all live in plastic houses? - Vale, Brenda (Architectural History Aotearoa, 2015)
In the 1950s plastics were hailed as a material for the modern home, whether in the form of Tupperware containers (early 1950s) or a vinyl Barbie doll (1959). However, modernism was traditionally built on the so-called "new" materials of glass, steel and concrete (all well known in one form or another to the Ancient Romans) with no mention of plastics. The 1950s saw plastics, their development boosted by World War II, enter the building industry, albeit often hidden in the form of glues and pipes. Attempts were made to produce the all-plastic house, such as the Smithsons' 1956 "House of the Future" for the Ideal Home Exhibition in London, which used plastic interiors within a more conventional shell, and Goody and Hamilton's 1957 Monsanto "House of the Future" made of fibre glass panels. This paper investigates these buildings and the attempts made to introduce plastics into 1950s homes in New Zealand, with an emphasis on advertising in Home and Building. It concludes by suggesting that plastics, with the exception of laminates, mostly remain hidden in the modern dwelling. It also suggests that New Zealand architects of the 1950s were reluctant to embrace the new materials, preferring an architecture based on natural, and preferably home sourced, materials.